Aquatic activities: contributions to treatment of individuals with chronic disease (Research, Society and Development, 2020)
This paper is about a study, of mixed method, evaluative-interpretative on transversality with the action-research, performed in the State of Bahia, during the period September-November/2015, the study aimed to evaluate the effects of hydrotherapy in pain perception and functionality of individuals with Osteoarthritis, registered in an interdisciplinary program of health care, and list the effects of this therapy on the markers of Systemic Arterial Hypertension HAS and Mellitus Diabetes DM of the assisted group. The participants, eight elderly women, ranging 63 years old, assisted according to the questionnaire Western Ontario and McMaster Universities Osteoarthritis Index WOMAC; Algofunctional questionnaire of Lequesne; Analog Visual Scale EVA; clinical record of evaluation of arterial pressure and capillary blood glucose; and systematic guideline of team observations. The results pointed improvement in the participant’s clinical condition, expressed by 40.8% of pain relief, 46.5% in joint stiffness and 37.3% in the difficulty degree to perform day-to-day activities, according to WOMAC, resulting in better functional capability and pain relief and knee joint stiffness, reinforced by 71% reduction of articular functional impairment, according to the Lequesne index. In EVA, the pain perception was 5.3 and went to 3.95 at the end of the hydrotherapeutic program. The HAS numbers proved themselves within advisable standards and the DM numbers presented reduction in one out of three of the existing cases. In conclusion, hydrotherapy potentially aided functional capability, pain relief and control of blood pressure levels of the participants, ratifying this therapy in health care.